FLAG FOOTBALL IN MASS SPORTS SYSTEM: POTENTIAL GROWTH OPPORTUNITIES - Borina, Y.Y.; Rybakova, E.O.; Sapegin, S.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the flag football progress and potential growth opportunities in the national mass sports system. Methods and structure of the study. We used the following methods for the purposes of the study: analysis of the relevant theoretical and practical study reports; analysis of the legal and regulatory framework for the physical education and sports sector; statistical reports; and summaries of the practical flag football implementation projects by the relevant physical education and sports organizations. Results and conclusion. The age group specific physical progress and health improvement needs make the modern flag football a highly appealing and beneficial sport discipline conditional on facilitating provisions to: Encourage progress of the American football / flag football groups and clubs; Make calendars of competitions and promote popular flag football events; Offer training and advancement programs for the flag football coaches; Facilitate regional American football / flag football progress initiatives with efficient municipal programs to support recreational/ popular sports movements; Make sure that the academic flag football is listed with the Student Games program in Russia; Expand and improve the legislative and regulatory framework to spur up the flag football progress. Modern flag football as a contactless version of American football is rather beneficial due to its popular and very accessible and affordable standards and rules that effectively encourage physical progress, motor activity and health of every population group.